Mathematical Model of Ion Transport in Electrodialysis Process - F. S. Rohman; N. Aziz (Bulletin of Chemical Reaction Engineering & Catalysis, 2008)
Mathematical models of ion transport in electrodialysis process is reviewed and their basics concept is discussed. Three scales of ion transport reviewed are: 1) ion transport in the membrane, where two approaches are used, the irreversible thermodynamics and modeling of the membrane material; 2) ion transport in a three-layer system composed of a membrane with two adjoining diffusion layers; and 3) coupling with hydraulic flow system in an electrodialysis 2D and 3D cell, where the differential equation of convectivediffusion is used. Most of the work carried out in the past implemented NP equations since relatively easily coupled with other equations describing hydrodynamic conditions and ion transport in the surrounding solutions, chemical reactions in the solutions and the membrane, boundary and other conditions. However, it is limited to point ionic transport in homogenous and uniformly - grainy phases of structure.  © 2008 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)